1975
DOI: 10.3181/00379727-149-38874
|View full text |Cite
|
Sign up to set email alerts
|

An Elevation of Plasma TSH Concentration in Spontaneously Hypertensive Rats (SHR)

Abstract: Thyroidal radioiodine uptake and release varied somewhat from strain to strain in rats, but no abnormal elevation or depression has been reported in rats (1). Okamoto (2) isolated a new strain from Wistar rats with spontaneous hypertension and noticed that this strain of rats had bigger thyroids, adrenals, and pituitaries than those of the control strain. Since coincidence of an increase of pituitary and thyroid weights suggests an increased production and release of TSH by the anterior pituitary, the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

1977
1977
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 1 publication
1
21
0
Order By: Relevance
“…SHR are characterized by several neuroendocrine abnormalities, including a chronic hypersecretion of TSH of unknown etiology associated with normal plasma T3 and T4 levels. 23 This inappropriately high TSH secretion in euthyroid SHR may be the result of an impaired hormone negative feedback regulation of the central TRH system or a inappropriate pituitary TSH production. 24 Accordingly to other authors and our own previous data, we showed that SHR in basal conditions present a higher (3-fold) plasma TSH concentration compared with control WKY rats.…”
Section: Discussionmentioning
confidence: 99%
“…SHR are characterized by several neuroendocrine abnormalities, including a chronic hypersecretion of TSH of unknown etiology associated with normal plasma T3 and T4 levels. 23 This inappropriately high TSH secretion in euthyroid SHR may be the result of an impaired hormone negative feedback regulation of the central TRH system or a inappropriate pituitary TSH production. 24 Accordingly to other authors and our own previous data, we showed that SHR in basal conditions present a higher (3-fold) plasma TSH concentration compared with control WKY rats.…”
Section: Discussionmentioning
confidence: 99%
“…Several variables were studied to determine if thyroid weight increases were secondary to hyperor hypofunction of the gland, with T 3 and T 4 serum levels being the most frequently measured. In spontaneously hypertensive rats, age-dependent variations (170) have been seen and contradictory results in adult rats have been reported (167,170,171). A decrease in T 3 and T 4 serum levels in Dahl rats (172) and a reduction in T 3 serum concentrations in encapsulated hypertensive rats (169) were observed.…”
Section: The Thyroid Gland and Blood Pressurementioning
confidence: 93%
“…In spontaneously hypertensive rats (167), mineralocorticoid (168) and renal encapsulated hypertensive rats (169), an increase in thyroid gland weight has been reported. A sigmoid relationship was observed between the ratio of thyroid weight to body weight and systolic blood pressure.…”
Section: The Thyroid Gland and Blood Pressurementioning
confidence: 99%
“…These include lowered levels of plasma thyroxine and triiodothyronine, elevated plasma thyroid-stimulating hormone, consequent increased thyroid weight and radioiodine uptake, 50 and impairment of synthesis or secretion of thyroid hormones in response to thyroid-stimulating hormone. 51 It is also noteworthy that Takeichi et al 19 proposed that the natural thymocytotoxic autoantibody they observed in many SHR is an IgM molecule, as indicated by its elution pattern on gel filtration and sensitivity to reduction by 2-mercaptoethanol.…”
Section: Discussionmentioning
confidence: 99%